Meningkatkan Kemampuan Berpikir Kritis Matematika Peserta Didik di Sekolah Dasar pada Era Digital - Tinambunan, Rani Rosaria; Pratiwi, Sarah; Ulandari, Neni; Ni’mah, Nadhira Tita An (Indonesian Journal Publisher, 2024)
This research aims to assess strategies for improving elementary school students' critical thinking skills using a literature review approach. Analysis of previous research related to critical thinking skills was carried out to identify more effective and efficient efforts. The hope is that the results of the literature review can provide valuable insight for educators in improving elementary school students' critical thinking skills. The research findings involved a review of 15 journals, with emphasis on reference sources, sample types, research methods, interventions, and journal review results. In conclusion, increasing students' critical thinking skills can be achieved through various learning models, such as Problem Based Learning, Discovery Learning, Problem Solving, Inquiry, and Cooperative, especially in the context of mathematics learning.